DAMPAK BULLYING TERHADAP PERCAYA DIRI PESERTA DIDIK SEKOLAH DASAR - Chan, Faizal; Kurniawan, Agung Rimba; Kalila, Siti; Amalia, Fiki; Apriliani, Devi; Herdana, Sonya Verta (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
AbstractÂ The purpose of this study is to describe the impact of bulliying on the confidence of elementary school students ". The impact of bullying can affect students' psychological development. Another impact of victims of bullying can be an offender for others. The research method used in this study is qualitative. This type of research used in this study is a purposive study because researchers feel the sample taken is most knowledgeable about the problem to be examined by the researcher. Based on the results of the study it can not be seen directly the impact of victims of bullying, but psychologically the victims of this bullying experience pressure. Even in some cases, victims of bullying do not have confidence.Â